Three years' follow up: relationship of maternal depression and anxiety with ever-wheezing - AY, NADİYE PINAR (My University, 2021)
Our previous data had not shown an association between wheezing during the first year life and maternal depression and anxiety. The aim of this study was to investigate the role of prenatal maternal depression and anxiety as risk factors for ever-wheezing in the first three years of life. Mother-infant pairs enrolled between 2016-2018 formed the population of this study (n=697). All subjects were phoned and questioned about wheezing and physician diagnosis of asthma. Age and maternal education, smoking habits, Edinburgh postnatal depression scale(EPDS) and State Trait Anxiety Inventory 1,2(STAI) scores during the last trimester were recorded from previous cohort data. Among 285 children enrolled, 84(%29.5) had ever-wheezing in the first 3 years of life. Mean age of wheezers and non-wheezers were 39.6±8.2 and 39.1±7.3 months respectively (p=0.13). Mean maternal age was not significantly different between the groups (p=0.16). 47,6% of ever-wheezers and %54.7 of non-wheezers were females (p=0.29). Family history of asthma was not signficantly different between the two groups (p=0.84). Current maternal smoking was reported by 40.5% of ever-wheezers and 41.3% of non-wheezers (p=1.0). Maternal smoking before and during pregnancy were 16.7% and 4.8% in ever-wheezers while 10.9% and 7.5% in never-wheezers respectively (p=0.33). Prenatal maternal depression was present in 17(20.2%) of ever-wheezers compared to 45(22.4%) of non-wheezers (p=0.75). Maternal depression and anxiety at three months postpartum were not significantly different (10.7 in wheezers,15.4% in non-wheezers, p=0.35). In conclusion, prenatal depression and anxiety was not related to ever-wheezing during the first three years of life.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Göğüs Hastalıkları ve Allerji; Medicine; Health Sciences; Internal Medicine Sciences; Chest Diseases and Allergy; SOLUNUM SİSTEMİ; Klinik Tıp; Klinik Tıp (MED); RESPIRATORY SYSTEM; CLINICAL MEDICINE; Clinical Medicine (MED); Solunum Bakımı; Akciğer ve Solunum Tıbbı; Respiratory Care; Pulmonary and Respiratory Medicine; Asthma; Children; Wheezing